Efektifitas dan Relevansi Pelatihan Pengembangan Madrasah Efektif pada Program AusAid SNIP MDC Jawa Barat - Ulfiah (Tarbiyah Departement collaboration with AMCA, 2016)
The background of research is the phenomena of madrasah decreasing in West Java to develop its capacity in the effectivity. The program of SNIP MDC in Effective School Improvement (ESI) gave encouraging and training to its effectivity. The purposes of this research are: 1) analyzing training effectivity of ESI; and 2) analyzing training relevancy toward its capacity. The research used qualitative approach by descriptive method. The source of data is madrasah as unit of analysis (such as principal, treasurer, and parent commitee), by techniques of interview, observation, checklist, and documentation. The conclusion are: 1) ESI training has good effectivity. That was showed by increasing post test based pre test, and knowledge increasing by good effect size; and 2) The increasing of relevance and effective has high index more than 80% and that showed by credit program fulfillment at 85,35%.